'Sometimes I can't look in the mirror': Recognising the importance of the sociocultural context in patient experiences of sexuality, relationships and body image after ovarian cancer. (5th July 2022) - Boding, Sally‐Anne; Russell, Hayley; Knoetze, Ricki; Wilson, Victoria; Stafford, Lesley
Abstract: Objective: Ovarian cancer (OC) can significantly change the way women feel about their body. However, personal accounts regarding these changes are lacking in the literature. Therefore, the aim of this study was to gain an understanding of the ways in which OC can affect relationships, sexuality, womanhood and body image. Methods: Ninety‐eight Australian women aged 18 and over diagnosed with OC completed an online survey that invited narrative responses to open‐ended questions about relationships, sexuality, body image and womanhood following OC treatment. Responses were analysed thematically while applying a sociocultural lens. Results: Three themes and two subthemes were identified: Failure and Loss of Femininity and Womanhood, Internalising Public Perception of Body and Illness and Altered Relationships which comprised two subthemes, Loss of the Sexual Self and Relationship Burden . These themes suggest women view themselves and their relationships in comparison with sociocultural understandings of body normalcy. Women often questioned their self‐worth, their relationships and place within society due to changes in fertility, sexuality and bodily functioning. Conclusion: These results highlight a need for health care professionals to open dialogue with women about sexuality and ensure information and support is given to reduce stigma and positively influence self‐perception and increase body acceptance.